(untitled) (Research, Society and Development, 2024)
Giant cell central granuloma is a benign intraosseous lesion with not very well-understood etiology that affects the gnathic bones, mostly occurring in females, generally in children or young adults, with the mandible being the most commonly affected bone. This lesion is characterized by the growth and destruction of bone tissue, causing asymmetry that may or may not present painful symptoms. The granuloma is classified into aggressive and non-aggressive lesions based on their clinical and radiographic characteristics. Lesions with aggressive characteristics exhibit rapid growth. The therapeutic option depends on several factors related to the lesion, such as size, affected region, duration of evolution, symptoms, and the presence of teeth. Generally, treatment involves intralesional corticosteroid injections or enucleation for smaller lesions, whereas for aggressive and large lesions, treatment involves resection and, when indicated, immediate reconstruction with bone graft. For the mandibular body and angle region, the iliac crest should be considered as the primary donor site for grafting due to its ample availability of bone and low complication rates associated with its removal. The aim of this study is to report a case of mandibular reconstruction using an iliac bone graft after extensive resection.